IDENTIFIKASI KARAKTERISTIK SEKTOR INFORMAL DI PROVINSI JAWA TIMUR - Dhika Amalia Kurniawan (UNIVERSITAS PGRI MADIUN, 2019)
This study aims to explore further information about the background, the profile of the informal sectors sector in east java. The identification results can be utilized in various matters : policy formulation, identify problems informal sectormapping of a strategy to build competitive advantage for informal sectors. This study used quantitative approach and the data collection techniques used are survey methods using questionnaires. Data analysis techniques is descriptive statistic test. The sample used is mostly informal sectors in east java by the number of samples used by 250 respondents. This study shows that the profile of informal sector business actors in East Java can be seen that based on the aspect of gender differences, informal sectors were dominated by respondents with female genitalia. Based on the aspect of marital status, informal sectoris dominated by married respondents with a percentage of 81.6%, based on the aspect of age distribution, informal sectors are dominated by respondents aged 40-49 years, with a percentage of 37.6%. Based on the aspect of education level, East Java informal sectorwas dominated by respondents with high school level education with a percentage of 62.8%. Based on the aspect of ownership of expertise before entrepreneurship, informal sectorwith the same percentage, the respondents already have expertise in entrepreneurship and some do not have expertise before trying. Based on the aspect of the number of full time workers in their business, East Java informal sectoronly has one worker in their business operations, with a percentage of 40.8%.Keyword : Informal Sector, East Java, Bussiness.